Pelatihan Manajemen Umkm Sebagai Upaya Peningkatan Ekonomi Pada Masa Pandemi Bagi Kelompok Wirausaha di Desa Jembrak - Heru Yulianto; Abdul Rauf; Dyah Palupiningtyas; Ray Octafian (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2022)
Small and Medium Enterprise (UMKM) in Indonesia is one of the cornerstones of the Indonesian economy. Semarang Regency has a lot of business potential which is the main source of livelihood for the local population. The purpose of this activity is to provide training for Small and Medium Enterprise (UMKM) in Jembrak Village regarding business ethics, bookkeeping of financial transactions, marketing of goods and services, product packaging and labeling, and taxation (E-Filing). The implementation method in this activity includes providing material on simple financial bookkeeping and mentoring programs on entrepreneurial activity and simple financial bookkeeping. The main target in this service activity is the business actors of UMKM in Jembrak Village and the wider community in general. The material presented by STIPARI Semarang lecturers in training on the topic of business ethics and simple bookkeeping takes approximately 120 minutes, followed by a question and answer session in three sessions. With this service activity, the authors provide recommendations for holding similar education to other different communities and the need for continuity of activities and evaluation after the community service activities are carried out, so that UMKM actors in Surabaya can contribute to the development of UMKM in Indonesia.